2021
DOI: 10.3389/fphys.2021.724828
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate 73 Promotes Anti-arrhythmic Effects of Voltage-Dependent Anion Channel Through Regulation of Mitochondrial Ca2+ Uptake

Abstract: Mitochondria critically regulate a range of cellular processes including bioenergetics, cellular metabolism, apoptosis, and cellular Ca2+ signaling. The voltage-dependent anion channel (VDAC) functions as a passageway for the exchange of ions, including Ca2+, across the outer mitochondrial membrane. In cardiomyocytes, genetic or pharmacological activation of isoform 2 of VDAC (VDAC2) effectively potentiates mitochondrial Ca2+ uptake and suppresses Ca2+ overload-induced arrhythmogenic events. However, molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…VDAC1 expression is up-regulated by elevated calcium ion levels [26] . VDAC1 and VDAC2 are differential proteins, and the voltage-dependent anion channel (VDAC) acts as a channel for the exchange of ions (including Ca2+) across the outer mitochondrial membrane [49] . The FC for VDAC2 was 6.2 with a P value of 0.037.…”
Section: Resultsmentioning
confidence: 99%
“…VDAC1 expression is up-regulated by elevated calcium ion levels [26] . VDAC1 and VDAC2 are differential proteins, and the voltage-dependent anion channel (VDAC) acts as a channel for the exchange of ions (including Ca2+) across the outer mitochondrial membrane [49] . The FC for VDAC2 was 6.2 with a P value of 0.037.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in STING and VDAC2 double‐depleted A498 cells, compared with WT‐VDAC2/WT‐STING, reconstitution with WT‐VDAC2/CACA‐STING (Figure S4N , Supporting Information) showed an increased mitochondrial calcium level due to the inability of CACA‐STING in binding and suppressing VDAC2 (Figure S4O , Supporting Information). On the other hand, E84Q‐VDAC2 was reported to be deficient in transporting calcium into mitochondria [ 47 ] and WT‐STING/E84Q‐VDAC2 reconstitution showed WT‐STING failed to bind and suppress E84Q‐VDAC2 induced reduction in mitochondrial calcium levels (Figure S4O , Supporting Information). These data further support the importance of STING/VDAC2 interactions in governing mitochondrial calcium homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…These studies revealed a transmembrane pore region composed of a 19-stranded β-barrel with an N-terminal α-helix lining the pore. The main differences among the three isoforms consist of (a) the absence of glutamate 73, recently linked to the ability of VDAC2 to control calcium flux across the OMM (201), in VDAC3, and (b) the presence of six cysteines in VDAC3 (54), proposed to confer an oxidative stress sensor function to this isoform (180,266). Thus, although the isoforms are structurally quite similar, subtle primary sequence differences may facilitate isoform-specific roles (e.g., 140,182).…”
Section: Voltage-dependent Anion Channels Of the Outer Mitochondrial ...mentioning
confidence: 99%